Optimization of multifunctional powing unit parameters - Malashikhin Nikolai; Yudina Elena; Papusha Sergey; Kadyrov Michael (BIO Web of Conferences, 2023)
Technology of soil moldboard plowing with a reversible plow with the simultaneous the main mineral fertilizer application, as well as additional crumbling of plowed layer and leveling the field surface, is substantiated. Using the modeling of operation process of complex plowing unit, its optimal parameters and operating modes are substantiated. Feature of the structural and technological scheme of the proposed unit is the use of reversible high-speed plow PSK with a reinforced frame structure, with a low energy intensity of the plowing process due to the elimination of plow land-sides, with devices for crumbling furrow slice and leveling field surface with simultaneous mineral fertilizer application. Incorporation and application of fertilizers into the soil without a break in time improves operation quality and reduces costs. Block diagram of algorithm for optimizing parameters and modes of proposed multifunctional plowing unit operation is presented and dependence of tractor engine power on its mass is approximated. Mathematical model and algorithm for optimizing the parameters and modes of complex unit operation have been developed, using as an optimization criterion, the minimum value of total energy consumption for the performance of operation process with a working speed limit of up to 15 km/h, plow working width of up to 6 m, plow specific resistance coefficient of up to 80 kN/m2, plowing depth of up to 0.3 m, fertilizer hopper capacity up to 4 m3, furrow length of up to 2 km. The K-701 tractor has been adopted as a power unit. At the minimum value of the optimization criterion, the following parameters have been substantiated: plow width, working speed, fuel consumption, performance, power unit tractive effort, traction power, fertilizer hopper capacity. Dependences of optimization criterion on the unit parameters and modes of its operation have been obtained.